HUBUNGAN ANTARA LATAR BELAKANG PENDIDIKAN FORMAL, PENGETAHUAN, STATUS EKONOMI DAN SIKAP DENGAN UPAYA MASYARAKAT MENGENAI BUDIDAYA Gyrinops versteegii (Gilg.) Domke DI PULAU LOMBOK - Taufik Samsuri (IKIP Mataram, 2013)
The purpose of this study was: (1) to reveal how formal educational background, knowledge, economic status, attitudes and efforts of the farming community farming Gyrinops versteegii (Gilg.) Domke on the island of Lombok. (2) to determine the relationship of formal educational background, knowledge, and attitudes to the economic status of the farming community efforts Gyrinops versteegii (Gilg.) Domke on the island of Lombok. This type of research is survey research design and descriptive quantitative descriptive correlational. Data were analyzed using descriptive statistics. While the relationship of formal education background, knowledge, economic status and attitudes correlated with community efforts on cultivating Gyrinops versteegii (Gilg.) Domke using bivariate product moment correlation test, followed by regression analysis using the aid package SPSS for Windows 00:17. Results of this study indicate that (1) the level of formal education background, at 25.71% with very low category, knowledge of 67.23% with enough categories, economic status by 50% with the low category, the attitude of 65.40% with enough categories, and cultivation efforts Gyrinops versteegii of 54.42% with low category. (2) The results of analysis of the association in this study showed that there is a significant relationship between formal educational background, knowledge, and attitudes to the economic status of efforts farming Gyrinops versteegii with correlation value of 0.898 and the coefficient of determination (R2) of 0.806.